2015
DOI: 10.1080/09540121.2015.1120268
|View full text |Cite
|
Sign up to set email alerts
|

Increased HIV testing among hospitalized patients who declined testing in the emergency department

Abstract: Health-care systems have serial encounters with many of the same patients across care settings; however, few studies have examined the role of reoffering HIV testing after a patient declines. We assessed whether an intervention to increase HIV testing among hospitalized patients was associated with increased testing among those who declined a test while in the Emergency Department (ED). We studied 8-week periods pre- and post-implementation of an electronic medical record (EMR)-based intervention to increase H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Other strategies, such as improved education and training of health care providers on how to offer the test and use of electronic medical records, are beyond the scope of our study but warrant evaluation because they have been shown to improve HIV test acceptance. 18,32,33 There are several limitations to this study. Our sample was limited to a convenience sample that depended on study personnel' s availability, which often excluded patients admitted on the weekend.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other strategies, such as improved education and training of health care providers on how to offer the test and use of electronic medical records, are beyond the scope of our study but warrant evaluation because they have been shown to improve HIV test acceptance. 18,32,33 There are several limitations to this study. Our sample was limited to a convenience sample that depended on study personnel' s availability, which often excluded patients admitted on the weekend.…”
Section: Discussionmentioning
confidence: 98%
“…23,30 Additionally, reoffering the test to those who initially decline on admission to the hospital is another strategy that may improve test acceptance. 32 Incorporating HIV testing as a routine part of care, such as through optout HIV screening, is widely recommended and would likely increase test acceptance as well. 2,5,6,18,19,33 According to the CDC, opt-out HIV screening includes notifying the patient orally or in writing that an HIV test will be done unless they defer or decline the test.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers can continue to strengthen HIV screening efforts among all persons in clinical settings and continue rescreening efforts among persons at high risk for HIV. Healthcare providers can incorporate HIV testing for all persons and for persons at high risk into standard clinical practice through institutional policy changes, electronic health record prompts, and provider education [25,26]. In non-clinical settings, public health practitioners can expand access to HIV testing, especially among populations at high risk for HIV, through strategies such as social marketing and networking and couples-based HIV testing and counseling [27], as well as promoting home testing [28].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HIV in those who underwent opt-out inpatient HIV screening was 0.4%, comparable to the estimated U.S. adult HIV prevalence and slightly higher than rates recently observed in opt-out screening programs in the United Kingdom and Singapore (Chua et al, 2012; Rayment et al, 2012), but significantly lower compared to the 8% observed among those undergoing targeted HIV testing in the ED in this study (p<0.001). While studies indicate that costs per HIV diagnosis and per transmission averted may be markedly higher in opt-out routine screening strategies compared to targeted testing (Gomez-Ayerbe et al, 2014), routine testing may identify more HIV infections, by identifying individuals who do not fulfill criteria for targeted testing (Felsen et al, 2015; Merchant et al, 2008; Oster et al, 2016). This was also shown in our study where opt-out inpatient screening identified 5 persons newly HIV diagnosed who had been admitted through the ED and had not received HIV screening.…”
Section: Discussionmentioning
confidence: 99%